2021
DOI: 10.5114/hm.2022.107981
|View full text |Cite
|
Sign up to set email alerts
|

Can muscle fatigue in women be influenced by knee extension tasks in different ranges of motion?

Abstract: Purpose. The present study aimed to compare the strength performance in the one-repetition maximum (1rM) test with a knee extension machine among different ranges of motion (rOMs), and to compare the force reduction after the performance of a dynamic exercise configured with different rOMs. Methods. Nine women (mean ± standard deviation: age: 24.2 ± 3.5 years; height: 166.5 ± 4.1 cm; body mass: 68.35 ± 4.14 kg) with no strength training experience and no history of injury performed (cross-over design) tests of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Whenever certain muscles are fatigued, a decreased task performance is expected (Pedrosa et al, 2022). For example, previous investigators showed that shoulder muscle fatigue decreased proprioceptive acuity in both hands (Sadler & Cressman, 2019), suggesting that distal upper limb performance could be affected by muscle fatigue from proximal joints that are responsible for limb movement stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever certain muscles are fatigued, a decreased task performance is expected (Pedrosa et al, 2022). For example, previous investigators showed that shoulder muscle fatigue decreased proprioceptive acuity in both hands (Sadler & Cressman, 2019), suggesting that distal upper limb performance could be affected by muscle fatigue from proximal joints that are responsible for limb movement stabilization.…”
Section: Introductionmentioning
confidence: 99%